2020
DOI: 10.3390/ncrna6030040
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA-Ribonucleoprotein Networks in the Post-Transcriptional Control of Gene Expression

Abstract: Although mammals possess roughly the same number of protein-coding genes as worms, it is evident that the non-coding transcriptome content has become far broader and more sophisticated during evolution. Indeed, the vital regulatory importance of both short and long non-coding RNAs (lncRNAs) has been demonstrated during the last two decades. RNA binding proteins (RBPs) represent approximately 7.5% of all proteins and regulate the fate and function of a huge number of transcripts thus contributing to ensure cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 73 publications
(160 reference statements)
0
32
0
Order By: Relevance
“…Studies have shown that lncRNAs can modulate gene expression by interac&ng with chroma&n and changing the genome architecture, sca9olding the regulatory proteins, and facilita&ng the recruitment of the regulatory proteins like RBPs 33 . RBPs are known to bind to chroma&nassociated RNAs and recently emerged as not only transcrip&on regulators but also as playing a role in genome architecture maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that lncRNAs can modulate gene expression by interac&ng with chroma&n and changing the genome architecture, sca9olding the regulatory proteins, and facilita&ng the recruitment of the regulatory proteins like RBPs 33 . RBPs are known to bind to chroma&nassociated RNAs and recently emerged as not only transcrip&on regulators but also as playing a role in genome architecture maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Nostrand et al 32 have shown that knockdown of an RNA binding protein (RBP) results in di9eren&al expression and alterna&ve splicing for genes with DNA binding sites for the RBP, sugges&ng that it mediates pre-and post-transcrip&onal regula&on at the chroma&n level. As lncRNAs have been known to regulate mRNA splicing and post-transla&onal modiFca&ons by interac&ng with the RBPs 33 , lncRNAs may play a role in recrui&ng RBPs to their target sites. Based on eCLIP data for K562 and HepG2 cells 32 we found 6,239 and 6,216 lncRNAs, respec&vely, with at least one RBP binding to it.…”
Section: Regulator Lncrnas Based On Chroma%n Associa%onmentioning
confidence: 99%
“…One of the best studied lncRNAs, Xist , can form ribonucleoprotein complexes (RNPs) in the nucleus to affect target gene transcription regulation [ 70 ]. It has been shown that lncRNAs can also be cytoplasmic and bind RBPs to affect other mRNA metabolism processes such as mRNA stability and turnover [ 71 , 72 , 73 ]. Depending on which factors interact with a given lncRNA, this could increase or decrease the targeted mRNA.…”
Section: Interaction Between Lncrnas and Rbps In Mrna Stabilizatiomentioning
confidence: 99%
“…Both in the nucleus and in the cytoplasm, lncRNAs may also act post-transcriptionally to modulate mRNA splicing (Figure 2D ), turnover or translation (Figure 2E ) by titrating RNA binding proteins (e.g. splicing factors, proteins involved in mRNA degradation) or by forming RNA-RNA hybrids with target pre-mRNAs ( 58 , 59 ). Some cytoplasmic lncRNAs act as ‘sponges’ of miRNAs: in light of the presence of miRNA binding sites in their sequence, such lncRNAs can physically sequester miRNAs, thus reducing their availability (Figure 2F ).…”
Section: Noncoding Rna Biology and Functionmentioning
confidence: 99%